2005
DOI: 10.1099/vir.0.80474-0
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic-cell infection by human cytomegalovirus is restricted to strains carrying functional UL131–128 genes and mediates efficient viral antigen presentation to CD8+ T cells

Abstract: Human cytomegalovirus (HCMV) genetic determinants of endothelial-cell tropism and virus transfer to leukocytes (both polymorphonuclear and monocyte) have been recently identified in the UL131-128 genes. Here it is documented that the same genetic determinants of HCMV are responsible for monocyte-derived dendritic-cell (DC) tropism, i.e. all endotheliotropic and leukotropic strains of HCMV are also DC-tropic (or dendrotropic). In fact, all recent clinical HCMV isolates and deletion mutants sparing the UL131-128… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
177
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 192 publications
(180 citation statements)
references
References 37 publications
3
177
0
Order By: Relevance
“…HCMVspecific T cell response is evaluated using as a stimulus autologous monocyte-derived immature DC infected with an endotheliotropic (Huv + ) and leukotropic (Leuk + ) HCMV strain [15].…”
Section: Introductionmentioning
confidence: 99%
“…HCMVspecific T cell response is evaluated using as a stimulus autologous monocyte-derived immature DC infected with an endotheliotropic (Huv + ) and leukotropic (Leuk + ) HCMV strain [15].…”
Section: Introductionmentioning
confidence: 99%
“…A critical breakthrough was represented by the identification of the PC, which consisted, as mentioned above, of the UL128L products complexed with gH and gL to form the PC-mediating entry complex for epithelial and endothelial [9] as well as dendritic [109] cells and M/M [110,111]. As a result, several investigators have suggested including the PC in vaccine designs [112].…”
Section: Development Of An Hcmv Vaccine: Potential Role Of the Pcmentioning
confidence: 99%
“…In human CMV (HCMV), for example, the UL146 chemokine is specific for ␣-chemokine receptors and can control dissemination of the virus in specifically chemoattracted neutrophils (16). There is another locus encoding a potential HCMV chemokine, UL131-128, and this also appears to affect endothelial, leukocyte, and dendritic cell (DC) tropism, in that passage in fibroblasts results in deletion or alteration at this locus (17)(18)(19). At least one transcript here encodes similarities to ␤-chemokines, which can chemoattract monocytes, and a similar function in murine CMV, vMCK, has been shown essential for virus dissemination (20 -22).…”
Section: H Uman Herpesvirus 6 (Hhv-6)mentioning
confidence: 99%